Predictive Ability of the Degree of Social ‎Media Websites Use and Level of ‎Psychological Hardness in Emotional Divorce ‎among a Sample of Married Women Working ‎at the University of Jordan - Almahaireh ‎, Abdallah; Alhasoun, Amal (Jordan Journal of Educational Sciences, 2021)
This study aimed to explore the degree of use of social media websites and the levels of psychological hardness and emotional divorce, as well as to identify predictive ability of the degree of social media websites use and level of psychological hardness in emotional divorce among a sample of married women working at the University of Jordan. The sample of the study consisted of (350) married women working at the University of Jordan in the first semester of 2018/2019. To achieve the aims of the study, the researchers developed three measures: A measure of the degree of use of social networking sites, a measure of psychological hardness, and a measure of emotional divorce. The study results showed a high degree of social media use and a medium level of both psychological Hardness and emotional divorce. In addition, the degree of social media use explained (54%) of emotional divorce, while psychological Hardness explained only (10%) of it